2016
DOI: 10.1007/s10897-016-9983-4
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Patient Harm in Canadian Genetic Counseling Practice: It's Time to Consider Regulation

Abstract: With the increasing awareness of genetic contributions to disease in Canada, the availability of and demand for genetic testing has soared. Genetic counseling is becoming a recognized and rapidly growing (yet unregulated) health profession in Canada. We hypothesized that the potential risk for harm to the public posed by genetic counseling practice in the province of Ontario is sufficient to consider regulation. The Ontario Ministry of Health and Long-Term Care (MOHTLC) sets criteria (both primary and secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…In addition, the models used for legal recognition of GCs in different jurisdictions can have a significant influence on the types of tasks that can be delegated or performed independently by GCs. Several different models of legal recognition and regulation of GCs are described in the literature,, 3,27,[35][36][37]39,55 and, although such recognition and regulation may enhance patient safety, the impact of different models on workforce capacity is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the models used for legal recognition of GCs in different jurisdictions can have a significant influence on the types of tasks that can be delegated or performed independently by GCs. Several different models of legal recognition and regulation of GCs are described in the literature,, 3,27,[35][36][37]39,55 and, although such recognition and regulation may enhance patient safety, the impact of different models on workforce capacity is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…27 The regulatory framework for GCs and genetic nurses was highly variable across jurisdictions, and a number of publications discussed different elements of legal regulation, professional recognition, registration, and licensure. 3,27,[35][36][37][38][39] Provider-population ratios for CGs were estimated as 0.3 FTE per 100,000 inhabitants in Chile and 0.6 FTE per 100,000 inhabitants in Australia, and it was argued that these ratios indicated a shortage. 22,23,28 Included studies reported the absolute number of CGs in Portugal (30 practicing), Chile (28 practicing), the United States (over 250 practicing survey respondents), and Australia (approximately 150 medical genetics fellowship graduates).…”
Section: Type and Number Of Genetics Specialistsmentioning
confidence: 99%
“…Consistently, the least satisfactory areas are opportunities for career advancement and salary. There is also literature related to concerns about a lack of respect and/or autonomy for genetic counselors (Atzinger et al, ) although recently genetic counselors have made the case for autonomy in their quest for regulation (Shugar et al, ).…”
Section: Where Are We Now?mentioning
confidence: 99%
“…There is growing recognition of GCs internationally, with recent moves to register the profession in Europe (Paneque et al, 2016;Pestoff et al, 2016). Despite this, genetic counseling is not a registered profession in many countries, including Sweden (Pestoff et al, 2016) and Canada (Shugar et al, 2017). Shugar et al (2017) Regulation of GC practice is important as more roles will involve GCs to be based in MDT as the genetics expert (Middleton et al, 2017;Patch & Middleton, 2018).…”
Section: Australian Gc Regulationmentioning
confidence: 99%
“…Despite this, genetic counseling is not a registered profession in many countries, including Sweden (Pestoff et al, 2016) and Canada (Shugar et al, 2017). Shugar et al (2017) Regulation of GC practice is important as more roles will involve GCs to be based in MDT as the genetics expert (Middleton et al, 2017;Patch & Middleton, 2018). Importantly, professional registration and GC certification in both the UK and USA have lead to more autonomous practice opportunities and recognition of GC ability (Baty, 2018) and ensures quality and safe practice (Professional Standards Authority, 2016).…”
Section: Australian Gc Regulationmentioning
confidence: 99%